1986
DOI: 10.1002/j.1460-2075.1986.tb04540.x
|View full text |Cite
|
Sign up to set email alerts
|

Restricted expression of EBV latent genes and T-lymphocyte-detected membrane antigen in Burkitt's lymphoma cells.

Abstract: Certain newly established Epstein‐Barr virus‐containing Burkitt's lymphoma cell lines do not express the cytotoxic T‐lymphocyte‐detected membrane antigen (LYDMA) through which EBV infection is normally controlled by the host. When the EB virus recovered from these BL lines was used to transform peripheral blood lymphocytes from seronegative donors, the lymphoblastoid cell lines (LCLs) that arose were all LYDMA positive. This indicates that the LYDMA‐negative nature of the BLs is not the result of a mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(110 citation statements)
references
References 42 publications
4
106
0
Order By: Relevance
“…However, the existence of discrete latency programs is strongly supported by studies of EBV-associated malignancies (Table 1). Thus, Latency III is expressed in the immunoblast-like cells of EBV carrying lymphoproliferative disorders arising in organ and bone marrow transplant recipients and HIV patients (Thomas et al, 1991), while Latency I is found in EBV carrying Burkitt's lymphomas (BLs) that are phenotypically similar to memory B lymphocytes (Rowe et al, 1986). In line with the germinal center origin of Hodgkin's disease (HD) lymphomas, cells from EBV-positive HD express a Latency II program (reviewed in Niedobitek et al, 2000).…”
Section: Ebv Latency and Oncogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…However, the existence of discrete latency programs is strongly supported by studies of EBV-associated malignancies (Table 1). Thus, Latency III is expressed in the immunoblast-like cells of EBV carrying lymphoproliferative disorders arising in organ and bone marrow transplant recipients and HIV patients (Thomas et al, 1991), while Latency I is found in EBV carrying Burkitt's lymphomas (BLs) that are phenotypically similar to memory B lymphocytes (Rowe et al, 1986). In line with the germinal center origin of Hodgkin's disease (HD) lymphomas, cells from EBV-positive HD express a Latency II program (reviewed in Niedobitek et al, 2000).…”
Section: Ebv Latency and Oncogenesismentioning
confidence: 99%
“…A genetically and phenotypically similar but EBV-negative variant of the tumor is found all over the world suggesting that EBV infection acts as a cofactor in the pathogenesis of this malignancy. Only EBNA-1 is usually detected in the EBV positive tumors (Rowe et al, 1986), although tumors expressing EBNA-1 together with the high molecular weight EBNA-3, -4 and -6 were recently described (Kelly et al, 2002). In all cases, the viral EBNA-2 and LMP-1 are not expressed and, as a result, EBV-positive BL cells do not express B-cell activation markers, adhesion and costimulatory molecules and grow as single cell suspensions rather than in clumps (Rowe et al, 1986).…”
Section: The Rescue Program: Lmp-2a and The Capture Of Cellular Ubiqumentioning
confidence: 99%
See 1 more Smart Citation
“…In type I latency, only the EBNA1 protein is expressed (64). It has recently been shown that EBNA1 peptides do not enter the major histocompatibility complex class I antigen processing and presentation pathway (29,39,52), and cells which express only EBNA1 are not detected by host cellular immune surveillance mechanisms (63).…”
Section: Epstein-barr Virus (Ebv) Infection In Immunocompetentmentioning
confidence: 99%
“…6 Upon prolonged cultivation in vitro the cells start to express the whole set of viral genes expressed in EBV immortalized lymphocytes (Group III) and as a consequence, start to express a variety of adhesion molecules and activation markers. 6,7 We have been interested to better understand to which degree EBV and the c-myc oncogene contribute to the phenotype and growth pattern of BL cells. To this end, we have attempted to reconstruct some of the essential features of BL cells in vitro starting from primary normal human B lymphocytes.…”
mentioning
confidence: 99%